Modeling and Control of the WPT System Subject to Input Nonlinearity and Communication Delay - Zhao, Shijun; Tang, Chunsen; Chen, Fengwei; Zhao, Dan; Deng, Pengqi; Xiao, Jing (IEEE transactions on power electronics, 2023)
Wireless power transfer (WPT) systems are a kind of high-order, highly nonlinear, time-delay systems. The conventional circuit theory-based methods for modeling the system results in high-order models, so it may not be efficient in digital implementation, especially on cost-sensitive micro-controllers. Besides, the time delay will impair the feedback performance of the system, and even lead to closed-loop instability under incorrectly compensated. To solve the above-mentioned problems, this article proposes to infer a low-order model for the system based on sampled data and then use this model to design the control system. More precisely, the proposed methodology consists of two steps: In the first step, a parsimonious modeling method is proposed to yield a low-order model of Hammerstein type plus time delay, which makes it possible to simulate the model response in a cost-sensitive micro-controller; Then, based on the model obtained in the previous step, the internal model control (IMC) is adopted to design the closed-loop control system. Benefited from the accurate prediction provided by the model, the closed-loop controller can mitigate the effect of the time delay and track the set value quickly. Finally, experimental and comparative results are given to verify the effectiveness of the proposed method.